The Effect of Human Resource Management and Principal Leadership on Improving the Quality of Education: (Study at Modern Islamic High School in Eastern Serang Regency) - Muhammad Miqdad Arromy; Agus Gunawan; Machdum Bachtiar; Anis Fauzi (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aims to determine the level of respondent achievement (TCR) on human resource management (HRM), principal leadership, and education quality as well as, to determine the effect of HRM, and/or principal leadership on improving the quality of education in Modern Islamic Boarding High Schools in Eastern Serang Regency. The method used is a survey method using a quantitative approach. The variables used in the study, namely the independent variables include HRM and principal leadership, and the dependent variable is the quality of education. The instrument used was a questionnaire with a Likert scale. Data analysis techniques used are descriptive statistical analysis techniques and inferential statistics include prerequisite tests in the form of normality tests and linearity tests, then simple regression analysis tests and multiple regression analysis tests. The results showed that 1) TCR on HRM is in the very good category with a value of 86.7%; 2) TCR on the principal's leadership is also in the very good category with a value of 87.2%; 3) Furthermore, TCR on the quality of education is in the very good category with a value of 89.3%; 4) there is a positive influence between HRM and the quality of education, namely by rejecting H0 because the significance value of 0.000 <0.05; 5) as well as there is a positive influence between the principal's leadership and the quality of education, namely by rejecting H0, because the significance value of 0.000 <0.05; 6) and there is a positive influence between HRM and principal leadership on the quality of education, namely by rejecting H0 because the significance value of 0.000 <0.05 and and Fhitung 23.548 greater than Ftable 3.32. The influence of HRM and principal leadership on the quality of education is 61.9%.